CAN THE ASEAN REGIONAL INTEGRATION LEAD TO A SINGLE CURRENCY IN SOUTHEAST ASIA? - Biondi S Sima (WANUA : Jurnal Hubungan Internasional, 2015)
Since 1991, talks on ASEAN regional integration grew tremendously and the weight of ASEAN countries in the world economy kept increasing. This became more pronounced in the growing interlinkages between ASEAN countries through Free Trade Agreements (FTA) that aimed to augment investment in the region and promote further economic liberalization. The ASEAN economic community starting in 2015 leads the way to even more opportunities to create “EU-like” region, having a common currency area. However the failures of the EU to cope with the recent global crisis and the substantial differences between this region vis à vis ASEAN raises many doubts. How would common currency area be feasible in ASEAN context and would it benefit the region in terms of economic development? The aim of this paper is to analyse the current achievements in the ASEAN in forming a unified bloc and the feasibility of a single currency in the region based on the Optimal Currency Area (OCA) criteria. Furthermore, it will examine possible alternatives that will help catalyse ASEAN economic integration, such as: tapping into smaller groupings among member states with more uniformed monetary policy and business cycle, ASEAN Swap Arrangements (ASA) and regional surveillance mechanism, adopting common currency peg, among others.